2023
DOI: 10.1186/s13018-023-03717-5
|View full text |Cite
|
Sign up to set email alerts
|

Daurisoline attenuates H2O2-induced chondrocyte autophagy by activating the PI3K/Akt/mTOR signaling pathway

Abstract: Background Osteoarthritis (OA) is a chronic degenerative joint disease characterized by cartilage degeneration and intra-articular inflammation. Daurisoline (DAS) is an isoquinoline alkaloid isolated from Rhizoma Menispermi, whose antitumor and anti-inflammatory pharmacological effects have been demonstrated, but the effects of DAS on OA have rarely been researched. In this study, we aimed to explore the potential role of DAS in OA and its partial mechanism. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Significantly, these genes were mainly enriched in cell death related BPs, including the cellular response to oxidative stress, superoxide metabolic process, and positive regulation of programmed cell death. Meanwhile, these genes were primarily engaged in pathways of cartilage homeostasis and chondrocytes death, such as MAPK, PI3K-Akt, and mTOR signaling pathways [ [28] , [29] , [30] ]. Further ClueGO analysis revealed that ferroptosis was associated with the pathways of fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, these genes were mainly enriched in cell death related BPs, including the cellular response to oxidative stress, superoxide metabolic process, and positive regulation of programmed cell death. Meanwhile, these genes were primarily engaged in pathways of cartilage homeostasis and chondrocytes death, such as MAPK, PI3K-Akt, and mTOR signaling pathways [ [28] , [29] , [30] ]. Further ClueGO analysis revealed that ferroptosis was associated with the pathways of fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Oroxin B reduced the expression of MMP-3 and MMP-13 by downregulating the production of p-PI3K and p-AKT in chondrocytes [75]. Daurisoline, an isoquinoline alkaloid, alleviated the HO-induced high expression of MMP-3 and MMP-13 and degradation of type II collagen [117]. Urolithin A downregulated the production of p-PI3K and p-AKT in chondrocytes and reduced the expression of ADAMTS-5 and MMP-13 [76].…”
Section: Pi3k/aktmentioning
confidence: 99%
“…Salvianolic acid B reduced IL-1β-mediated inflammatory cytokine production in chondrocytes in osteoarthritis and protected osteoarthritis progression ( Lou et al, 2017 ). Daurisoline activated the PI3K/Akt/mTOR axis and led to inhibition of H2O2-mediated autophagy in chondrocytes ( Zhang et al, 2023b ). Oroxin B suppressed the PI3K/Akt/mTOR pathway and induced autophagy and anti-inflammation, leading to inhibition of osteoarthritis progression ( Lu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%